Identifying and Prioritizing Research to Improve Emergency Care of Persons Living With Dementia: A Geriatric Emergency care Applied Research 2.0 Network ‐ Advancing Dementia Care (GEAR 2.0‐ADC) Scoping Review. (20th December 2022) - Gifford, Angela; Shah, Manish N; Carpenter, Christopher R; Dresden, Scott M; Dussetschleger, Jeffrey; Leggett, Jesseca; Taylor, Zachary; Hwang, Ula
Abstract: Background: Persons living with dementia (PLWD) frequently access emergency departments (EDs) for care, but current research surrounding their unique care needs is limited. The Geriatric Emergency care Applied Research 2.0 Network–Advancing Dementia Care (GEAR 2.0‐ADC) aims to identify and prioritize research gaps surrounding the most important needs for PLWD to advance their emergency care. Method: A Task Force of 61 stakeholders including ED‐ and non‐ED‐based clinicians, PLWD, care partners, and advocacy organizations was established. Task Force members voted to choose the top four topics for investigation. Two Patient‐Intervention‐Comparison‐Outcome (PICO) questions were developed per topic. Following the PRISMA‐ScR guidelines and working with medical librarians, systematic literature searches and scoping reviews were completed by Task Force members. Findings were presented at the GEAR 2.0‐ADC Consensus Conference to the full Task Force. After discussion, they developed research questions for each topic area and voted to prioritize the questions within each topic area for future investigations. Results: Task Force voting identified four critical topics for investigation and two unique PICO questions for each topic. The literature search and abstraction process comprehensively summarized the research to date for dementia detection (3, 651 identified, 132 abstracted), communication and decision‐making (8, 138 identified, 24 abstracted), ED clinical practices (6, 348 identified, 23 abstracted), and care transitions from the ED to the community (3, 484 identified, 10 abstracted). General themes that emerged from the abstraction process included a need for effective patient‐centered care interventions in the ED and when transitioning back to the community following care, identification of communication barriers between care partners and medical staff, measurement of dementia in the ED setting that is both efficient and operational, a need to decrease stimulation, and for increased PLWD and care partner engagement. The stakeholders rank‐voted the research questions developed for each topic, resulting in a framework for GEAR 2.0‐ADC's support for future research. Conclusion: Transdisciplinary stakeholders, PLWD, and care partners identified critical research topics and performed four scoping reviews, leading to refinement of the research gaps and prioritization for future research. These gaps will be addressed in upcoming GEAR 2.0‐ADC funding opportunities.